How to choose an appropriate drug dosage form for the treatment of respiratory infections in children: Facts and tips - Cvijić, Sandra; Mirković, Dušica; Krajišnik, Danina (Archives of Pharmacy, 2022)
The treatment of respiratory infections in children requires special attention, since the paediatric population has rather specific characteristics and consists of heterogenous subgroups. In this context, the choice of a suitable drug dosage form is of particular importance, depending on the active substance properties, along with the age and general condition of a paediatric patient. Тhe most commonly used pharmaceutical products for respiratory infections in children include oral, parenteral and inhalation dosage forms, although a large number of drugs are not available in a suitable dosage form and/or strength for paediatric age, leading to the frequent use of unauthorized drugs (i.e., unlicensed use). Other important issues that should be considered when choosing the appropriate paediatric dosage form and/or compounding procedure are related to the careful considerations of the pharmaceutical product composition (safety of excipients) and the choice of administration/dosing device in relation to a child’s age. This paper provides an overview of paediatric dosage forms used in the treatment of respiratory infections in children, their benefits and limitations. The review includes examples of various pharmaceutical products, along with the considerations regarding administration/dosing devices. Specific characteristics of paediatric populations affecting the decision on the choice of age-appropriate paediatric formulation are also addressed.